Consumers' perception of vitamin D and fortified foods. Issue 9 (24th July 2019) - Clark, Beth; Hill, Tom; Hubbard, Carmen
Abstract : Purpose: As natural dietary sources of vitamin D are not consumed in sufficient quantities, fortified foods could play a role in maintaining vitamin D sufficiency. With public consultation, an integral part of designing acceptable fortification strategies, the purpose of this paper is to understand public awareness and perception of vitamin D fortified foods. Design/methodology/approach: A mixed-methods approach was taken with two focus groups and 109 surveys conducted using a non-probability sample from North-East England. Thematic analysis of focus group data identified six themes, with factor and cluster analysis identifying seven factors and four clusters, respectively, which highlighted differences in vitamin D knowledge and fortified food perceptions. Findings: Despite identifying sunlight as the main vitamin D source (91 per cent), participants were less aware of the main dietary source (33 per cent), and few could state fortified products (51 per cent). Although attitudes towards fortification were generally favourable (63 per cent agreeing that selected products should be fortified), nearly half (43 per cent) were unsure if more products should be made available. Results suggest that more natural products to complement existing market offerings would be most preferred. Factor and cluster analysis results identified awareness of health benefits and/or dietary sources as essential to have favourable attitudes towards fortified products. Originality/value: This research adds to the limited literature regarding consumer attitudes towards fortified foods. It highlights a need to improve public awareness and labelling of fortified products to potentially increase fortified food consumption.